Impulsivity links reward and threat sensitivities to substance use: a functional model - Richardson, George B.; Freedlander, Jonathan M.; Katz, Elizabeth C.; Dai, Chia-Liang; Chen, Ching-Chen (Frontiers in Psychology, 2014)
This study used structural equations modeling and undergraduate student data to examine the effects of reward and threat sensitivities on substance use, along with the extent to which impulsivity explained these effects. Our results suggest that impulsivity may translate inversely related reward and threat sensitivities into substance use, completely mediate the effect between threat sensitivity and substance use, and partially mediate the effect between reward sensitivity and substance use. Our results also suggest that individuals with a combination of higher levels on both reward and threat sensitivities may be most impulsive and vulnerable to substance use. We discuss implications for research at the interface of personality and substance use and also substance abuse prevention and treatment.